2017
DOI: 10.23938/assn.0010
|View full text |Cite
|
Sign up to set email alerts
|

Characterising people who demanded the rapid HIV test in Andalusia between 2013 and 2014

Abstract: Fundamento. El objetivo del estudio fue caracterizar a las personas que demandaron la prueba rápida VIH en Andalucía.métodos. Estudio trasversal realizado por las entidades sociales colaboradoras del Programa de diagnóstico precoz del VIH en Andalucía. Los participantes fueron personas que demandaron la prueba en fluido oral y que contestaron una encuesta previa a la misma entre septiembre de 2013 y agosto de 2014. Se realizó un análisis descriptivo y de regresión logística para determinar los factores de ries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…were more likely to have been tested in the past year, which was consistent with the results of many studies (Lorusso et al, 2017;Sun et al, 2020;Wong et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…were more likely to have been tested in the past year, which was consistent with the results of many studies (Lorusso et al, 2017;Sun et al, 2020;Wong et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, 66.8% (2,674/4,005) of the participants had been tested for HIV in the past year. Multivariate analysis showed that MSM with high-risk behaviors such as anal sex with men in the last 6 months and drug use were more likely to have been tested in the past year, which was consistent with the results of many studies ( Lorusso et al, 2017 ; Sun et al, 2020 ; Wong et al, 2017 ). A study reported that 51% of MSM living in the United States had been tested for HIV in the past year ( Stephenson et al, 2015 ).…”
Section: Discussionsupporting
confidence: 88%